Escrita e classificação de repertório para sopros à luz da tabela de parâmetros técnicos - Cláudio Fernandes Lage (2012)
This study was developed focused on the repertoire for Winds and Percussion groups, observing the Bands historical aspects around the world, such as in Brazil, also discussing about the system of grades for repertoire according to the technical difficult. To discuss about the grades aspects were analyzed scores published by international publishers who adopted different ways to specify the technical difficult, dialoguing with the Table of Technical Parameters, published by FUNARTE. In complement to the discussion of the system of grades, were also analyzed three works made under the recommendations of the Table of Technical Parameters. Also, was discussed the flexibility to treat the parameters at the different grades in which the three works are classified.